2009
DOI: 10.1371/journal.pone.0004457
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Integration Regulating Male Courtship Behavior in Drosophila

Abstract: The courtship behavior of Drosophila melanogaster serves as an excellent model system to study how complex innate behaviors are controlled by the nervous system. To understand how the underlying neural network controls this behavior, it is not sufficient to unravel its architecture, but also crucial to decipher its logic. By systematic analysis of how variations in sensory inputs alter the courtship behavior of a naïve male in the single-choice courtship paradigm, we derive a model describing the logic of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
127
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(136 citation statements)
references
References 68 publications
(96 reference statements)
9
127
0
Order By: Relevance
“…However, if a moving female abdomen is presented in front of the male, then the tethered male will exhibit sustained courtship-like pursuit until the target female stops 'moving' 8 . These results indicate that the courtship-like pursuit is visually guided 4,8 . In the present experiments, we found that a tethered male displayed sustained courtship-like pursuit even when the target female was replaced with a moving squareshaped light spot displayed on a screen (Fig.…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…However, if a moving female abdomen is presented in front of the male, then the tethered male will exhibit sustained courtship-like pursuit until the target female stops 'moving' 8 . These results indicate that the courtship-like pursuit is visually guided 4,8 . In the present experiments, we found that a tethered male displayed sustained courtship-like pursuit even when the target female was replaced with a moving squareshaped light spot displayed on a screen (Fig.…”
Section: Resultsmentioning
confidence: 60%
“…Visual motion typically results in orienting and chasing behaviours, which are often accompanied by unilateral wing extension and vibration, two hallmarks of courtship behaviour [1][2][3][4] . However, such courtshiplike behaviour quickly wanes unless the moving object is a female [1][2][3][4] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Inspection of video sequences indicated that these classes of behaviors often involve physical contact between the fore-and middle legs of the interacting flies, and these were scored to evaluate their relative frequency of occurrence (Table S1). Drosophila legs harbor both touch-and tastesensitive sensillae (13), suggesting that flies might exchange somatosensory and gustatory information during these interactions.…”
mentioning
confidence: 99%
“…The gustatory mutant poxn ΔXBs6 has a deletion of the poxn gene with a partial transgenic rescue that effectively transforms gustatory sensillae, including those on the forelegs, into mechanosensory sensillae (13). The control Canton-S and Oregon-R females formed interactions at a significantly higher rate than males (P < 0.001), and Canton-S flies made interactions more frequently than Oregon-R flies (P < 0.001).…”
mentioning
confidence: 99%